An instrument to assess supply chain risk: establishing content validity. (1st January 2011) - Manikandan, L.; Thamaraiselvan, N.; Punniyamoorthy, M.
Organisations are forming supply chain networks for delivering the right quantity of quality products at the right time to their customers. An understanding about the potential risk sources which could possibly disrupt the performance of the entire supply chain would be useful when developing an instrument to assess the supply chain risk. The objective of this paper is to develop an instrument and establishing the content validity by a quantitative method. The instrument is developed for the purpose of assessing the overall supply chain risk of firms which are grouped under heavy engineering industry.